Diabetes mellitus and pregnancy in Wolfram syndrome type 1: a case report with review of clinical and pathophysiological aspects - Caretto, Amelia; Scarascia Mugnozza, Francesca; Valsecchi, Fanny; Pedone, Erika; Pozzoni, Mirko; Rosa, Susanna; Laurenzi, Andrea; Frontino, Giulio; Chimienti, Raniero; Piemonti, Lorenzo; Scavini, Marina (Frontiers in Medicine, 2025)
Wolfram syndrome type 1 (WS1) is a rare genetic disorder characterized primarily by non-autoimmune diabetes mellitus, optic atrophy, deafness, and diabetes insipidus. It may include other endocrine, urological, psychiatric, and neurological disorders. The syndrome arises from mutations in the WFS1 gene, which encodes the Wolframin protein, a key regulator of endoplasmic reticulum (ER) function in pancreatic beta-cells and other tissues. Diabetes in WS1 typically has an early-onset, progresses slowly, and is characterized by insulin deficiency, low insulin requirement, and a lower incidence of chronic complications compared to type 1 autoimmune diabetes. Nowadays, there is no cure for WS1, and management relies on the treatment of the different associated conditions. Fertility can be compromised due to hypogonadism, although cases of successful pregnancy have been reported. These are high-risk pregnancies due not only to hyperglycemia, but also to the other comorbidities of the WS1. This review discusses the peculiarities of diabetes associated with WS1 and the reproductive outcomes in WS1, reporting a case of successful pregnancy in a woman with WS1 treated with a hybrid closed-loop insulin pump.